Enhancing digital competence and learning motivation of master’s students: a new educational model for Kazakhstan’s higher education system - Bakirova, Zakira; Tasova, Asel; Absatova, Marfuga; Sadirbekova, Dinara; Auezov, Batyrkhan; Meirbekova, Gulmira (Frontiers in Education, 2026)
This study introduces and empirically validates a comprehensive educational model designed to enhance digital competence and learning motivation among Master’s students in Kazakhstan. Using a quasi-experimental design with 236 participants from five pedagogical universities, the research examined how an integrated approach combining technology-enhanced pedagogy, microlearning, gamification, online assessment, and collaborative digital projects influenced students’ digital competence, learning motivation, and academic performance. Results demonstrated significant improvements in digital competence across all dimensions (effect size η2 = 0.46) for students in the experimental group, with particularly strong development in content creation and problem-solving competencies. The model also had a positive influence on learning motivation, self-efficacy, student engagement, and academic performance. Path analysis confirmed an integrated theoretical framework where technology-enhanced pedagogy influenced digital competence, which subsequently affected motivation, self-efficacy, engagement, and academic achievement. Students with elementary baseline digital skills showed the largest competence gains, indicating the model’s potential for addressing digital inequality in Kazakhstan’s higher education system. Follow-up assessments revealed durable effects, suggesting sustainable rather than transient changes. The research provides theoretical contributions to understanding the interrelationship between digital competence and motivation while offering practical strategies for modernizing Master’s programs in Kazakhstan and similar educational contexts.